Bowalization: Its Impact on Soil, Biodiversity, and Human Livelihoods in West Africa - PADONOU, Elie Antoine; Mette Lykke, Anne; BACHMANN, Y.; SINSIN, Brice (My University, 2015)
Bowal (plural bowé) is a particular form of degraded land on hardened ferruginous soils (ferricrete) found in tropical regions with unimodal precipitation. It is characterized by ferricrete exposure due to soil surface erosion. The drivers for bowé establishment are deforestation, intensive monocrop production and/or climatic dryness. Bowé are characterized by reduced water retention capacity and electrical conductivity, low organic matter, nitrogen, silt and extractable phosphorus but high amounts of exchangeable potassium and increased soil temperature. Bowalization leads to loss of biodiversity and changes in vegetation structure. The vegetation on bowé is characterized by annual herbaceous plants and trees with impeded roots growth and structural adaptions (e.g Combretum nigricans develops more stems, more branches and larger crown diameter on bowal compared to surrounding soils). Bowalization has negative consequences for crop production. Farmers in West Africa have adopted methods for growing cowpea and groundnut on bowé using a hoe for manual tillage and weed control. Livestock herders exploit the short season with annual grasses and practice transhumance or use food supplies during the dry season. Bowalization is predicted to persist and increase in extent in the future.
Keywords: Bowé; Plant biodiversity; Crop production; Livestock rearing; Adaption practice; Land degradation